Metaphor in Parable from the Noble Qur’an: A Corpus Based Stylistic Approach - Dewi Suriyani Djamdjuri; Zuriyati Zuriyati; Siti Gomo Attas (Islamic Religious Education Departement, 2022)
A compelling speech figure, a parable, or a metaphor in the Qur'an seeks to explain a crucial point by sticking in the mind and helping us absorb the message and firmly lodge it in our hearts. The stylistic method utilized in this study was a corpus-based stylistic method, which entails a contextual assessment of the term or pattern in issue. The information is based on passages from the Qur'anic corpus that have been translated into English. The stylistic corpus-based approach was used to investigate four different types of metaphor. They are standard, implied, visual, and extended metaphors, as evidenced by the findings. From the result finding it shows that there are 21 verses in the metaphor that are classified as standard metaphors, accounting for 61% of the metaphor. There are 5 verses, or 13%, of implied metaphor, 7 verses, or 18%, of visual metaphor, and 3 verses, or 8%, of extended metaphor. The metaphor that appeared the most frequently is a standard metaphor.